Penerapan Pendekatan Montessori untuk Menanamkan Pemahaman Konsep Bilangan Cacah pada Siswa TK Putera Zaman Malang - Dyah Ayu Sulistyaning Cipta (IAIN Ambon, 2018)
Abstract Teaching counting lessons to kindergarten students is often considered taboo. Some people assume that should not teach counting lessons to children who have not even reached the age of seven years. A long debate arose due to an elementary school admission test that contained numerical questions. Is it true that kindergarten students are not allowed to learn numeracy lesson? The purpose of this study is to introduce a montessori approach, a feasible approach used to teach the concept of counting in kindergarten students. This research is a qualitative descriptive research conducted on TK A Putera Zaman students. The research begins with the conduct of obeservasi and interview, then proceed with applying montessori approach in learning done with teacher in class. The results of the research with the stand on the opinion of Maria Montessori that the early age to the age of six years is the phase Absorbent Minds, the child's brain will continue to change, grow rapidly, and open to new stimuli, so kindergarten A students have learned to count. Some steps to embed the concept of counting to the students of Kindergarten A Putera Zaman can be done with the following delivery steps: (1) Introduction to quantity 1 - 10, (2) What is zero, (3) Matching numbers with quantity 0 - 10, (4) Relation of 1 – 10, (5) Basic sum operation, and (8) Basic reduction operation. The result of cultivating the concept of chopping with montessori approach is that students can use mathematics based on reasoning, not just counting without logic. Keywords: montessori, concept, whole number, counting atkindergarten